2014
DOI: 10.3329/medtoday.v26i1.21301
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Hyponatremia in Hospitalized Diabetic Patients- A Cross Sectional Study

Abstract: Hyponatremia is a very common electrolyte imbalance in admitted diabetic patients which leads to substantial morbidity and mortality. There is no existing record for profiling of hyponatremia in Bangladeshi diabetic subjects. The objective of this study was to find out the factors influencing hyponatremia and associated co-morbidities in admitted diabetic patients of a tertiary care hospital. Samples were selected from all adult nonpregnant diabetic patients with serum sodium level < 135 mmol/L irrespective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“… 6 , 24 , 25 Due to the osmotically active nature of glucose, diabetes can cause a drop in serum Na + levels by causing a dilution effect that moves water from intracellular to extracellular compartments. 26 However, our study finding was lower than studies done in Bangladesh (63.3%) and Kerala (75%). 27 , 28 The difference could be those studies done in admitted diabetic patients included diuretics medication takers and the majority of participants had diabetic nephropathy, both of which are major contributors to hyponatremia.…”
Section: Discussioncontrasting
confidence: 89%
“… 6 , 24 , 25 Due to the osmotically active nature of glucose, diabetes can cause a drop in serum Na + levels by causing a dilution effect that moves water from intracellular to extracellular compartments. 26 However, our study finding was lower than studies done in Bangladesh (63.3%) and Kerala (75%). 27 , 28 The difference could be those studies done in admitted diabetic patients included diuretics medication takers and the majority of participants had diabetic nephropathy, both of which are major contributors to hyponatremia.…”
Section: Discussioncontrasting
confidence: 89%
“…Similarly, a female preponderance was also seen in other studies, while others showed no sexual preference for hyponatremia. [17][18][19] Grikinienė et al demonstrated a clear-cut predilection for the feminine gender in cases with hyponatremia. Moreover, females are most vulnerable to brain damage from hyponatremia and are more liable to have brain demyelination (ODS), as a result of excessive therapeutic correction of hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the impairment of their main transport system, Sahid SM and Mahboob T 2008 [3] proposed progressive patterns in electrolyte abnormalities in diabetes mellitus leading to end stage renal disease. Diabetes can lower serum Na+ levels by creating a dilution effect that shifts water from intracellular to extracellular compartments because glucose is osmotically active [4] . In contrast to patients without anemia, people with anemia had lower salt and potassium levels, according to Mansoor F et al 2021 [5] .…”
Section: Introductionmentioning
confidence: 99%